2010
DOI: 10.3109/02770903.2010.489245
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Exhaled Nitric Oxide Levels (FeNO) in Childhood Atopic Asthma: Evidence for Neonatal Respiratory Distress as a Factor Associated With Low FeNO Levels

Abstract: Besides confirming the well-known tight association between blood eosinophilia and/or allergic sensitization and FeNO, these data provide new evidence for neonatal respiratory distress as potential factor associated with low FeNO levels in childhood atopic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…One study of 52 children aged 5–36 months demonstrated significantly higher FeNO levels in children with a positive asthma predictive index (API) compared to those with a negative API, although the median levels in both groups were low at 12.5 and 5.6 ppb, respectively [34]. FeNO levels have been described to be higher in allergic or atopic asthma compared to nonallergic asthma [45], but are also elevated in children who have allergic sensitization as demonstrated by positive skin-prick testing or aeroallergen-specific IgE [32,35,43]. FeNO levels have been shown to be higher in children with allergic sensitization or atopy and no asthma compared to nonallergic asthma [32,35,45], and have been found to be higher in children both with treated and untreated asthma than in healthy nonatopic children [54].…”
Section: Feno and Diagnosis Of Asthmamentioning
confidence: 99%
See 2 more Smart Citations
“…One study of 52 children aged 5–36 months demonstrated significantly higher FeNO levels in children with a positive asthma predictive index (API) compared to those with a negative API, although the median levels in both groups were low at 12.5 and 5.6 ppb, respectively [34]. FeNO levels have been described to be higher in allergic or atopic asthma compared to nonallergic asthma [45], but are also elevated in children who have allergic sensitization as demonstrated by positive skin-prick testing or aeroallergen-specific IgE [32,35,43]. FeNO levels have been shown to be higher in children with allergic sensitization or atopy and no asthma compared to nonallergic asthma [32,35,45], and have been found to be higher in children both with treated and untreated asthma than in healthy nonatopic children [54].…”
Section: Feno and Diagnosis Of Asthmamentioning
confidence: 99%
“…A history of neonatal respiratory distress in preterm infants without bronchopulmonary dysplasia (BPD) may lead to lower FeNO levels in children with atopic asthma, as described in a study by Ricciardolo et al [43]. A similar finding of lower FeNO levels was previously reported in school-aged children with BPD compared to controls [55], while Filippone et al found that FeNO levels were similar and normal among former preterm (defined as ≤32 weeks gestation) adolescents with BPD, former preterm adolescents without BPD and healthy adolescents born at term, a finding that held true even in the presence of atopy [56].…”
Section: Feno and Diagnosis Of Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Filiponne et al [16] have shown that children born prematurely with and without BPD have increase oxidative stress compared to children born at term despite normal eNO levels, pointing to other inflammatory pathways that cannot be picked up by eNO measurements. Ricciardlo et al [33] investigated determinants of eNO in childhood atopic asthma. They found that neonatal respiratory distress has been associated with low eNO in children with atopic asthma [33].…”
Section: Discussionmentioning
confidence: 99%
“…Ricciardlo et al [33] investigated determinants of eNO in childhood atopic asthma. They found that neonatal respiratory distress has been associated with low eNO in children with atopic asthma [33]. The higher eNO and V’ NO in long-term (≥7 days) than in short-term (<7 days) ventilated infants may have been caused by established ongoing inflammation secondary to prolonged intubation and mechanical ventilation as well as exposure to supplemental oxygen [34].…”
Section: Discussionmentioning
confidence: 99%